Thermal plasma torches : design, characteristics, application - Zhukov, M. F. (Mikhail Fedorovich); Zasypkin, I. M. (Cambridge International Science Pub., 2007)
The results of experimental research of plasma torches are described. A simple classification of linear plasma torches is proposed. Engineering methods of processing experimental data are outlined together with the electrical and thermal characteristics of plasma torches of different design in criterial form. Special attention is paid to the problems of plasma torch stability to extend their operating life. The characteristics of individual types of the design of plasma torches are discussed. The operating properties and description of plasma-chemical reactors and plasma torch reactors for var.